L'arbitrato internazionale. La questione della legge applicabile - Lombardi, Francesca (Università di Pisa, 2014)
la tesi tratta dell'arbitrato internazionale, partendo dall'analisi delle varie definizioni presenti nelle Convenzioni Internazionali e analizzando il procedimento arbitrale in questione si passa alla trattazione della questione relativa alla legge applicabile a tale tipo di arbitrato; sia a livello procedurale che a livello sostanziale.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrato internazionale; Legge applicabile; Legge applicabile all'arbitrato internazionale; Procedimento arbitrale internazionale

The transfer of movables in the international commercial context – a comparison of German and South African law - Lengyel, Martin (University of Johannesburg, 2014)
L.LM. (International Commercial Law) Please refer to full text to view abstract
Keywords: Contracts (International law); Germany; International Commercial Law; Law of property; Property; South Africa

Análise comparativa de modelos de governação corporativa no sector bancário moçambicano: os casos dos 3 maiores bancos - Mucheca, Elisa Vicente; Costa, Jeremias Cardoso Da (Universidade Eduardo Mondlane, 2014)
This paper aims to identify corporate governance models adopted by commercial banks in Mozambique. Firstly, it reviews the literature on Corporate Governance evolution, concept, models and practices at international level. It then makes an approach to internal control systems, some corporate governance arrangements such as Board of Directors, audit committees, internal and external auditing. The paper goes ahead to identifying the corporate governance practices both at country and banking sector levels. An explanatory analysis was applied as the research method covering three major commercial in terms of business volume, net profit and liquid assets. In order to gather information pertaining Corporate Governance models as well as on internal control systems, a questionnaire was sent to some commercial banks’ senior managers and to Banco de Moçambique as the monetary and supervisory authority of the credit institutions and financial societies in the country. Virtual and documental source were reviewed to assess the problem. The paper’s main finding is that commercial banks in Mozambique adopt the Anglo-Saxon model in which the Board of Directors is comprised of two types of directors, board committees and an array of information disclosure. Based on the main finding it was recommended a review and update by the competent authorities of the Aviso 11/GGBM/99 that prescribes internal control rules to be observed by credit institutions and financial societies in Mozambique. This paper aims to identify corporate governance models adopted by commercial banks in Mozambique. Firstly, it reviews the literature on Corporate Governance evolution, concept, models and practices at international level. It then makes an approach to internal control systems, some corporate governance arrangements such as Board of Directors, audit committees, internal and external auditing. The paper goes ahead to identifying the corporate governance practices both at country and banking sector levels. An explanatory analysis was applied as the research method covering three major commercial in terms of business volume, net profit and liquid assets.In order to gather information pertaining Corporate Governance models as well as on internal control systems, a questionnaire was sent to some commercial banks’ senior managers and to Banco de Moçambique as the monetary and supervisory authority of the credit institutions and financial societies in the country. Virtual and documental source were reviewed to assess the problem.The paper’s main finding is that commercial banks in Mozambique adopt the Anglo-Saxonmodel in which the Board of Directors is comprised of two types of directors, board committees and an array of information disclosure. Based on the main finding it was recommended a review and update by the competent authorities of the Aviso 11/GGBM/99 that prescribes internal control rules to be observed by credit institutions and financial societies in Mozambique
Keywords: Bancos comerciais; Controlo interno; Governação corporativa; Moçambique

Les mesures anti paradis fiscaux concernant les personnes morales - Sellier, Mathilde (Université de Reims Champagne-Ardenne, 2014)
La milliardaire New-Yorkaise, Leona Hemsley, disait à l’époque « Les impôts, c’est pour les petites gens ». Cette phrase prend tout son sens concernant les paradis fiscaux. Comment, dans un contexte de crise économique actuelle, les acteurs politiques et économiques peuvent-ils négliger ce fléau et ne pas en faire leur priorité. Si l’on en croit les chiffres actuels, les français détiennent environ 350 milliards d’euros offshore. Ce recours aux paradis fiscaux ne cesse de s’accroître avec le temps, malgré différentes conventions signées entre plusieurs États, voulant mettre fin à ces techniques d’évasion fiscale. Mais face à un tel échec, la question est alors de savoir comment agir et surtout, de quelle manière agir afin de dissuader et d’empêcher l’évasion des capitaux vers des pays à fiscalité plus légère et soumise au secret bancaire. Il s’agira ici d’étudier les techniques employées afin d’éviter l’imposition du fisc français. Cette étude passera notamment par le constat de mesures de luttes trop peu dissuasives engendrant un manque à gagner énorme pour les pays victimes de l’évasion fiscale, participant ainsi à l’enrichissement colossale des fraudeurs. Le but ici n’est pas de juger la politique inefficace des différents pays à l’égard des paradis fiscaux mais de mesurer l’ampleur des pertes engendrées et d’imaginer des mesures de lutte efficaces afin d’agir de manière irréversible contre ces évadés fiscaux. Cela passera notamment par une inévitable coopération entre les différents États qui feront de la lutte contre les paradis fiscaux leur priorité. En effet, il s’agira par exemple d’envisager des mesures d’embargo contre certains paradis fiscaux dans le but d’obtenir des informations jusqu’ici secrètes et de faire cesser leurs activités. Une confrontation entre les mesures actuelles et celles à venir en France mais aussi en Grande Bretagne et aux États-Unis apparaît alors indispensable pour mener à bien cette guerre. Il n’en reste pas moins que cette guerre, pour être gagnée, doit inévitablement passer par une plus grande contrainte, une lutte contre les sociétés-écrans ainsi qu’une plus grande vérification. Ces mesures ne devant pas être envisagées seules mais cumulativement.
Keywords: Droit comparé; Droit des affaires; Fraude fiscale; Paradis fiscaux

Proposal for a regulation on a common European sales law - Ciceri, Eliane (LUISS Guido Carli, 2014)
Historical development. Five W of CESL. Common European sales law.

L’hardship clause nei principi UNIDROIT - Milazzo, Federica (LUISS Guido Carli, 2014)
Il contratto commerciale internazionale. La clausola hardship. Analisi comparata dell’hardship nei vari ordinamenti.

Alle origini della mediazione - Donati, Viola (Università di Pisa, 2014)
L’esigenza di alleggerire il carico dei tribunali mediante forme di soluzione diverse e alternative al processo giurisdizionale trae le sue origini da esperienze culturali remote: l’arte della composizione del conflitto rappresenta un'attività di cui l’uomo si è fin da subito dovuto occupare, per lo meno dal momento in cui ha cominciato a vivere all’interno di una comunità, proprio perché si tratta di un’attività che sfiora tutti gli aspetti della vita sociale. La mediazione ha origini antichissime, infatti la necessità di sviluppare nei secoli procedure alle quali ricorrere per garantire un'ordinata convivenza e armonia sociale risale già all'antica Roma del V secolo A.C.: la prima delle XII Tavole (il più antico diritto scritto dell’antichità romana), richiama il tentativo di compromesso da esperirsi davanti al pretore con cui le parti in lite trovano un accordo sull’oggetto del contendere, nel qual caso il giudice è tenuto a consacrarlo con l’emanazione della sentenza mentre in caso di mancato raggiungimento di un accordo allora si sarebbero adite le vie giudiziali instaurando il processo. Le origini della mediazione trovano fondamento in tempi antichi anche in Paesi dell’estremo oriente ed in particolare in Cina dove la mediazione fu lo strumento principale nella risoluzione delle dispute: Confucio sosteneva che il modo migliore per dirimere una disputa fosse la persuasione morale e il raggiungimento di un accordo, piuttosto che la coercizione del Sovrano. L’idea stessa di “compromesso” è profondamente radicata nella cultura cinese, infatti non tener in alcun conto gli interessi dell’altra parte è considerato particolarmente deplorevole sul piano etico-giuridico ed il pensiero confuciano è promotore della mediazione, tanto che l’istituto continua tuttora ad essere praticato nella Repubblica Popolare Cinese. In tempi più recenti, dopo l’unificazione del Regno d’Italia e la conseguente stesura del codice di procedura civile del 1865, il legislatore ha dedicato ampio spazio alla composizione bonaria delle controversie, disciplinando la conciliazione nel titolo preliminare all'art.1, dando vita così alla figura professionale del giudice conciliatore: caratteristiche essenziali del procedimento consistevano nella compresenza della funzione conciliativa con quella giurisdizionale nel giudice conciliatore, la municipalità del giudice stesso e infine la completa assenza di formalità (il rito si svolgeva verbalmente) per consentire a tutti un facile accesso alla procedura. Se invece apriamo il Codice di procedura vigente, per trovare un accenno alla conciliazione bisogna aspettare l'art. 320, e questa sfiducia a cui è andata in contro la figura del giudice conciliatore è arrivata fino ai nostri giorni. Negli USA la mediazione fu introdotta come sistema volontario (nelle controversie sindacali tra le compagnie ferroviarie e i loro dipendenti) nel 1887, con la legge sul commercio tra gli Stati (Intestate Commerce Act), e a partire dalla fine degli anni ’60 trovò un applicazione sempre maggiore. Ma la svolta fondamentale si ebbe nel 1998, in occasione della modifica del Titolo 28° della Carta dei Diritti e nell'Alternative Dispute Resolution Act, che consacrarono il successo della cultura alternativa della gestione del conflitto nella società americana. Oggi il ricorso agli A.D.R. ha portato ad una riduzione del contenzioso giudiziario di quasi il 90%. Visto l’esito positivo avutosi oltreoceano, nell’aprile del 2002 la Commissione Europea ha presentato un Libro Verde relativo ai modi alternativi di risoluzione delle controversie in materia civile e commerciale per promuovere l’utilizzo della mediazione, ed in seguito alla Direttiva n. 2008/52/CE il governo italiano ha emanato il D.lgs. 28/2010 al fine di coordinare le disposizioni vigenti in materia di mediazione e conciliazione in ambito civile e commerciale, solo che appena due anni dopo, il 6 dicembre 2012, la Corte costituzionale ha dichiarato l'illegittimità del decreto per eccesso di delega legislativa, così che il governo Letta ha cercato di disciplinare nuovamente l'istituto con la Legge n.98/2013, sebbene stavolta la mediazione sia stata prevista come temporanea perché contemplata come obbligatoria per i soli quattro anni successivi alla sua entrata in vigore, a metà dei quali il ministero di giustizia avvierà un monitoraggio per valutare se la sperimentazione della procedura di mediazione ha funzionato. Speriamo che intanto la “cultura della mediazione” cominci a diffondersi anche in Italia.
Keywords: ADR; Conciliation; Conciliazione; MARC; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation

النقابة بين الشراكة الإجتماعية والنضال المطلبي - جعفور, ليندة; بوعزيز, ليندة (جامعة مولود معمري, 2014)
النقابة منظمة مهنیة هدفها حمایة حقوق العمال و ترقیتها ، بوسیلتین الأولى سلمیة تتمثل في الش ا ركة الإجتماعیة والتفاوض الجماعي، أما الثانیة مطلبیة حیث یستعمل العمال كل وسائل الضغط المتاحة على المستوى الوطني والدولي ، في حالة عدم الإستجابة لمطالبهم. Résumé . Le syndicat est une organisation professionnelle, qui a pour objectif la protection et la promotion des droits des travailleurs , par deux voie la première est celle du partenariat social, et de négociation collective , et la deuxième est revendicative ou les travailleurs utilisent tous les moyens de pression a l’échelle nationale et internationale, dans le cas ou leurs revendications non satisfaites.
Keywords: Grève; Lutte ouvrière; Négociation collective; Partenariat social; Syndicat; الإضراب; التفاوض الجماعي; الشراكة الإجتماعية; النضال المطلبي; النقابة

The strategic importance of regional economic integration to multinational companies (MNCs) : a study of South African MNCs' operations in the SADC - Egu, Mathew Eleojo (University of South Africa, 2014)
Though the strategic importance of regional economic integration to multinational companies (MNC) has been researched extensively internationally, this concept has not been studied in South Africa. In fact, there is a growing nostalgia that with the South African Development Community (SADC) moving towards its set macroeconomic convergence targets; regional economic integration eventually leads to macroeconomic stabilisation. This ultimately becomes the root of growth in a region that has been severely affected by globalisation, financial crises, increasing government debt and budget deficit problems. This study, hence, tries to find out how the critical decisions of South African MNCs are made when operating within regional markets. Consequently, statistical econometric models were developed to test time-series data from 1980-2011 using the best (most efficient) linear unbiased estimator (BLUE) ordinary least square regression technique. An analysis was then done to investigate how South African firms have been able to gain maximum benefits by adopting the SADC as its major trading bloc in Africa. The study’s findings showed that the major barriers that impede MNCs of South African origin from penetrating these markets were custom duties, direct and indirect tariffs. It was observed that this would only be reduced by regional integration. Determined to critically interrogate the problems detailed in this research, three hypotheses were tested, analysed and subsequent interpretation of the findings revealed that South African MNCs contribute positively to regional economic growth and investment in the SADC. Furthermore, the study found out that although these factors were important, they were not the only variables that stimulated the competitiveness of South African MNCs in the SADC region. The literature review sections of this study found that the adoption of strategic management initiatives by MNCs improved the operation of transnational companies in South Africa. A comparison between the value of South African MNCs, as well as, other explanatory variables, and the Gross Domestic Product (GDP) of both South Africa and the SADC using time series data for the period 1980-2011 indicated that there was a positive relationship between the contribution of MNCs to South Africa’s economy and the GDP of both South Africa and the SADC. This proved that there is a significant link between MNC growth and national/regional productivity. In conclusion, the study established that the findings of the literature review were theoretically in sync with the empirical analysis. Also, the outcome of this study concurred with the findings of similar research. In essence, regional trade arrangements are an increasingly important element of the global trade environment, of which the move by South Africa’s MNCs to operate in the SADC market was a positive one. Finally, the study found out that for these firms to be successful in the international business arena, business management decisions need to be made, only after a detailed strategic analysis of the significance of regional economic integration is considered. This integrative framework certainly determines the operational efficiency, survival and profitability of most MNCs that operate within the region.
Accepted: 2014-10-01T07:01:54Z
Keywords: FDI; Foreign direct investment; Macroeconomic convergence; Macroeconomic stability; Mergers & acquisitions; Multinational companies; Regional Economic Community; Regional Trade Agreements (RTAs); SADC; South Africa Development Community; Strategic management

La fiscalité des aides interentreprises - Andriamanantenasoa, Andotiana (Université de Reims Champagne-Ardenne, 2014)
Les entreprises ont une place importante dans l’économie française, pourtant la notion d’« entreprise » n’a jamais été définie par le législateur. Une entreprise peut être une structure privée ou publique. Elle a le choix entre diverses formes juridiques, mais quelle que soit son activité, sa taille, son régime d’imposition, une entreprise doit se préserver et doit toujours agir dans son propre intérêt. C’est cet « intérêt » de l’entreprise que l’Administration fiscale s’évertue à contrôler dans les opérations qu’elle effectue. Or, cette notion est elle-même difficile à appréhender. En la matière, les débats doctrinaux sont venus nourrir une jurisprudence peu abondante. Les règles relatives de la fiscalité des aides interentreprises ne distinguent pas selon qu’elles soient consenties entre sociétés sur le territoire français, ou qu’elles soient transfrontalières. Toutefois, les enjeux des aides interentreprises en matière internationale sont incontestablement différents de ceux des aides interentreprises nationales. Ce mémoire traite d’abord de la question du régime général de la fiscalité des aides interentreprises, pour ensuite étudier l’encadrement particulier des aides interentreprises transfrontalières.
Keywords: Aides interentreprises; Droit des affaires; Fiscalité des entreprises

Le divorce du chef d'entreprise individuelle marié sous le régime de la communauté des biens réduite aux acquêts - Salla, Ndèye Aminata (Université de Reims Champagne-Ardenne, 2014)
L’étude de ce mémoire porte sur le divorce du chef d’entreprise individuelle marié sous le régime légal de la communauté de biens réduite aux acquêts. Si l'entreprise correspond à une réalité économique, très souvent, on va évoquer le régime de la notion et les éléments qui la composent sans jamais au préalable définir ce qu’est une entreprise du point de vue juridique. Elle semble pouvoir être définie comme une structure sans personnalité juridique, composée d'un ensemble de biens et de personnes permettant la réalisation d'opérations qui caractérisent une activité professionnelle. Mais l'entreprise n'est pas pour autant dépourvue de valeur et celle-ci, au regard des régimes matrimoniaux, est forcément propre ou commune. Le choix de la forme juridique se fera entre l'immatriculation sous forme d'entreprise individuelle, ou sous forme de société. Le divorce entraîne de nombreuses conséquences tant patrimoniales qu’extrapatrimoniales. L’entreprise, et plus particulièrement celle exploitée sous forme individuelle, n’échappe pas à cet événement. Or, les conséquences financières d’un divorce peuvent se révéler tout aussi dévastatrices que celles d’une procédure collective (redressement judiciaire, liquidation judiciaire) non seulement pour l’entreprise elle-même mais, avant tout, pour le dirigeant, pour son conjoint et ses collaborateurs. Il s’agira d’expliquer dans un premier temps que le sort de l’entreprise individuelle dépend de sa nature. À savoir si elle est un bien est propre au chef d’entreprise ou un actif de communauté. À un moment où la communauté n'existera plus, comment sera gérée l’entreprise le temps de procéder au partage ? Le sort des biens non encore partagés et des revenus qu’ils génèrent est en effet source d’interrogations; Par ailleurs, il peut s’avérer que le conjoint du chef d’entreprise individuelle participait avant le divorce à l’exploitation de l’entreprise. Comment seront évalués et partagés les biens dans ces conditions ou chacun des deux protagonistes a intérêt à se voir attribuer l’entreprise au moment du partage ? Quelles sont les conséquences d'un divorce sur la pérennité de l'entreprise ? Pour répondre à ces questions, les analyses juridiques et financières dont le champ d’investigation est l’entreprise familiale au sein de laquelle l’époux entrepreneur exerce son activité professionnelle sont indispensables.
Keywords: Communauté de biens; Divorce; Droit des affaires; Entreprise

The compatibility of Australian and South African private international law with the Hague Principles on Choice of Law in International Commercial Contracts - Adams, Faadhil (University of Johannesburg, 2014)
In 2006 the governing body of the Hague Conference on Private International Law furnished the Secretariat with a mandate to conduct a series of feasibility studies on the development of an instrument, relating to the choice of law in international contracts. The outcome of these studies was largely successful, finding that there was a need for an instrument of this nature and additionally it would be welcomed by the international legal community. In 2009 the Permanent Bureau of the Hague Conference on Private International Law was invited to form a Working Group (WG) to draft a soft-law instrument affirming party autonomy in international contracts on an international level. The Hague Principles on Choice of Law in International Commercial Contracts (P) was, thus, born. The P were drafted by a panel of experts representing the majority of the world’s legal systems. The working group commentary (WGC will be used to refer to the commentary, whilst WG will be used to refer to refer to the working group itself) which provided the discussions in respect of, and the reasoning behind, the principles has been invaluable in writing this dissertation. The purpose of this dissertation is to investigate the compatibility of Australian and South African law with the P. One of the aims of the P mentioned specifically in the preamble is that these principles are to be used by countries as a model with which to develop their own rules of private international law. A study of the current law as it stands in comparison to the P marks the first step in this exercise, through finding where the law differs we can begin to bridge the disparity between a specific country’s legal system and that of the P. Should the P become an important part of the private international law discourse comparative studies such as this will become common-place. The fact that the principles were drafted as a soft-law instrument is in line with the growing world trend. The flexibility that is achieved through the use of a soft-law instrument may lead to greater legal certainty down the road as contracting parties and international lawyers alike become more familiar with the principles. This familiarity may lead to consensus among experts from around the world and eventually invite the prospect of a binding instrument being drafted
Keywords: Australia; Conflict of laws; Contracts; Contracts (International law); South Africa

La résolution du contrat de vente en droit OHADA : d’une réforme à l’autre - Ebata, Rodrigue N. (Université de Montréal, 2014)
La présente étude examine une des difficultés que soulève la résolution du contrat de vente en droit africain des affaires. L'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) créée par le Traité du 17 octobre 1993 organise les règles communautaires relatives à la résolution du contrat de vente. Le Livre VIII de l’Acte uniforme OHADA portant sur le Droit commercial Général a été adopté le 15 décembre 2010 et a abrogé l’Acte du 17 avril 1997. Selon l’article 281 de l’Acte uniforme, la résolution du contrat de vente ne survient que lors de l’inexécution totale ou partielle de l’obligation du cocontractant. Notre étude visera à évaluer les conséquences dans le droit de la vente OHADA de la substitution du critère de privation substantielle par celui de la gravité du comportement du débiteur justifiant une résolution unilatérale du contrat. Cette nouvelle position du droit de la vente OHADA se démarque dans une certaine mesure du droit matériel uniforme et rejoint un courant adapté aux impératifs socioéconomiques du commerce tant régional qu’international. En outre la partie lésée devra déterminer la gravité du comportement du débiteur au risque de voir sa demande sanctionnée pour défaut de droit et donner lieu à des dommages intérêts à l’autre partie. En effet, avec pour optique la nécessité de sauvegarder le contrat au nom du principe favor contractus, comment le juge détermine a posteriori si la gravité du comportement du cocontractant est suffisante pour anéantir le contrat? Ce nouveau critère de la gravité du comportement du cocontractant en droit de la vente OHADA vient supplanter le critère de la privation substantielle et fait cohabiter la traditionnelle résolution judiciaire avec celle de la résolution unilatérale dont les contours demeurent incertains. Les cas d’ouvertures liés à la résolution du contrat de vente OHADA pour inexécution des obligations fondamentales ou accessoires seront passés au crible de même que leurs effets sur les parties. Dans une approche comparatiste avec la Convention de Vienne et les règles de codifications privés telles que les Principes UNIDROIT ou du Droit Européen des Contrats il y a lieu de s’interroger sur la mise en œuvre et les conséquences de la résolution du contrat de vente OHADA par l’inexécution de l’obligation d’une des parties due à un manquement essentiel d’une part et à la gravité du comportement du débiteur d’autre part. The Treaty on Harmonisation of Business Law in Africa signed on October 17th, 1993 created the Organisation for Harmonisation of Business law in Africa (OHBLA).OHBLA organises common rules on resolution of sales contracts. The Book VIII of the Uniform act on General Commercial Law adopted on December 15th, 2010 replaces the previous act of April 17th, 1997. According to article 281 of this uniform act, contract resolution only occurs when there is a partial or total non execution of one party’s obligation. The present study is going to examine one of the difficulties that exist in the resolution of sales contracts in African business law. Our study will consist in evaluating the consequences of substitution of the substantial privation criteria by the seriousness of the debtor’s behaviour in OHBLA sales law. This substitution justifies a unilateral contract termination. This new OHBLA law position somehow distinguish itself from material uniform law and joins a new position socioeconomically more adapted to regional and even international business. Moreover, the prejudiced party will have to determine the gravity of the debtor’s behaviour risking to be punished for lack of motives and according damages to the other party. In fact, in order to save the contract by all means according to the favor contractus principle, how will the judge subsequently determine if the debtor’s behaviour gravity is enough to breach the contract? This new criterion of the gravity of a contracting party’s behaviour comes in replacement of the substantial privation criteria and enhances the cohabitation of the traditional judiciary termination and the unilateral cancellation which is still uncertainly defined. Cases related to contract resolution caused by non-execution of mandatory or accessory obligations in OHBLA law will be carefully examined as well as their effects on contracting parties. In a comparative approach with the Vienna Convention and private codifications such as UNIDROIT principles or European contract law, we will wonder about the use and the consequences of resolution of sales contract in OHBLA law caused by non-execution a mandatory obligation on one part and the gravity of one party’s behaviour on the other part.
Keywords: African law; Business law; CISG; CVIM; Commerce international; Commercial law; Contract; Contrat; Contrats internationaux; Droit africain; International business; International sales; OHADA; OHBLA; Resolution; Résolution; Sales; Sales law; UNIDROIT; Vente; Vente internationale

La résolution en ligne des conflits de consommation à l'aune de l'accès à la justice - Iavarone-Turcotte, Cléa (Université de Montréal, 2014)
Dans son sens le plus courant, mais aussi le plus étroit, la résolution des conflits en ligne (RCL) réfère à la migration, vers Internet, des modes alternatifs de règlement des conflits. Notre mémoire se concentre sur la transposition, en ligne, des seuls modes amiables de règlement des différends, dont font notamment partie la négociation et la médiation. La question guidant notre étude consiste à savoir si la résolution en ligne permet d’accroître l’accès du consommateur québécois à la justice. La première partie répond par l’affirmative, en démontrant en quoi la RCL permet de surmonter plusieurs obstacles à la fois objectifs et subjectifs auxquels se heurte le consommateur québécois souhaitant obtenir justice. Nous y présentons également certaines critiques récurrentes en matière de RCL et y répondons. Si cette première partie aborde essentiellement la question du pourquoi il est opportun de recourir au règlement électronique des litiges de consommation dans une perspective d’accès à la justice, la seconde s’intéresse à celle du comment. Notre hypothèse est que si le recours à la RCL est souhaitable pour améliorer l’accès du consommateur québécois à la justice, ce mode de règlement ne pourra véritablement porter ses fruits que s’il est encadré par l’État. Nous démontrons ainsi l’opportunité d’une intervention étatique en matière de règlement en ligne des différends de consommation. Selon nous, seule l’institutionnalisation de la RCL permettra de lever, en partie du moins, les barrières qui ont freiné, jusqu’à maintenant, le déploiement à grande échelle de ce procédé de règlement novateur. According to its most common, but also most narrow definition, Online Dispute Resolution (ODR) refers to the electronic form of Alternative Dispute Resolution (ADR). Our master’s thesis focuses on the online version of consensual dispute resolution processes, among which negotiation and mediation are found. The question underlying our research is the following: does ODR increase Quebec consumers’ access to justice? The first part of our study gives a positive answer to this question, by demonstrating how ODR can tackle many obstacles, both objective and subjective, to Quebec consumers’ access to justice. It also provides answers to the most frequent criticisms of ODR. This first part essentially addresses the question of why ODR can enhance consumers’ access to justice, while the second part focuses on the how. Our hypothesis is that ODR’s numerous advantages with regards to consumers’ access to justice will only truly materialize in practice if the government intervenes to regulate this dispute resolution method. We therefore demonstrate the opportunity of a State involvement in the field of consumer ODR. In our opinion, institutionalizing ODR will lift, partially at least, barriers that have hindered, to this day, the large-scale deployment of this innovative dispute resolution process.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/10372/Iavarone-Turcotte_Clea_2013_memoire.pdf
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Consommateur; Consumer; Consumer disputes; Contrôle étatique; Cyberjustice; Différends de consommation; Government control; Internet; ODR; Online Dispute Resolution; Regulation; Role of the State; Réglementation; Résolution des conflits en ligne; Rôle de l’État; Technologie; Technology

Cessão da garantia bancária autónoma: uma reflexão à luz do direito santomense - Jesus, Waldemar Eduardo (Universidade Nova de Lisboa, 2014)
La cession de la garantie bancaire autonome, est sans doute un aspect de la plus grande pertinence pour le cessionnaire d'un crédit accordé, c’est un autre moyen que le commerce, «máxime», le commerce international met à ses exploitantes ou ses operateurs pour obtenir de la liquidité. Nous espérons avec ce travail, d'analyser l'applicabilité de la garantie bancaire autonome, en partant du principe selon lequel en cas de transfert de crédit, les respectives garanties et autres accessoires également se transmettent. Basé sur la doctrine internationale, notamment italienne et portugaise, nous avons l'intention de parvenir à une solution que permet une application correcte de l'institut concerné, dans le cadre droit Santoméen, c'est à dire, c'est qui permet au cessionnaire d'une créance de protéger, effectivement, ses intérêts légitimes. A cessão da garantia bancária autónoma é, sem dúvida, um aspeto da maior relevância para o cessionário de um determinado crédito pois, é mais um meio que o comércio, «máxime», o comércio internacional dispõe aos seus operadores para obter a liquidez. Pretendemos com o presente trabalho, analisar a aplicabilidade à garantia bancária autónoma do princípio segundo o qual, em caso de transmissão de um crédito as respetivas garantias e outros acessórios também se transmitem. Com base na doutrina internacional, sobretudo italiana e portuguesa, pretendemos chegar uma solução que permita boa aplicação do instituto em causa na ordem jurídica santomense, isto é, que permita ao cessionário de um crédito salvaguardar, efetivamente, os seus legítimos interesses.
Keywords: Cession; Cessão; Crédit; Crédito; Garantia bancária autónoma; Garantie bancaire autonome; L’ordre juridique Santoméen; Ordem jurídica santomense

Addressing the legal issues of an innovative start-up company - Samoylov, Vlad (Victoria University of Wellington, 2014)
Before examining the substance of the law it is necessary to discuss the contrast between law and practice. It is important to keep in mind that the letter of the law is sometimes not what is done in practice. This realisation is often referred to as the “law and society perspective.” Advocates of this perspective treat legal doctrine as more than just a closed system because they recognise that there are other external influences at play. Beyond the law, people are also influenced by other factors such as social roles, morals, religion and culture. For example, university researchers have an external incentive mechanism outside of IP law. Such researchers frequently prefer to publish their results and discoveries in academic journals rather than file for patents. A patent cannot be granted where there has been a publication. However the researchers are motivated by other incentives such as access to research funds and the attainment of professorship. The Law and Society perspective highlights the fact that the formal processes, which are provided for by the law are at times substituted by informal customs and understandings. An information technology (IT) firm that contributed to this paper by participating in an interview (Interviewee A), provided a good example of such an occurrence. Rather than use any of the formal IP modes of protection which are discussed in the following sections of this paper, ‘Interviewee A’ uses a very unorthodox strategy to protect their IP. They said: “we rely on employment contracts, code of conduct, and especially personal ethics and behaviour to protect our IP. We therefore have a company culture that encourages teamwork and cooperation”.
Keywords: Intellectual property; Product safety standards

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

Conflictos de jurisdicción : juez del concurso vs administración pública - Aguilar Moya, Rocío Isabel (Universidad Internacional de Andalucía, 2014)
Trabajo de Curso de Experto Universitario en Derecho Concursal (2013). Tutor: Elena Narváez Valdivia. El principio de universalidad ha supuesto la atribución de competencia y jurisdicción al Juez del Concurso de todo aquello que tenga incidencia en el patrimonio del deudor, ello implica que materias que en un principio son competencia de otros órganos administrativos o jurisdiccionales, pasen a formar parte del ámbito de competencia del Juez del Concurso. El presente trabajo tiene como principal finalidad dar a conocer algunos ejemplos de Conflictos de Jurisdicción, señalando que preceptos tanto de la Ley Concursal como de la normativa administrativa, en la mayoria de los casos la Ley General Tributaria, entran en conflicto y cúal es el criterio seguido por el Tribunal de Conflctos de Jurisdiccion. Cabe señalar que algunos de estos casos ya han sido resueltos desde el año 2006, pero que todavía se siguen planteando en la práctica diaria. La investigación de dicha temática parte del concepto general de jurisdicción, del ámbito de jurisdicción y competencia de los Jueces de lo Mercantil; pasando por los mecanismos de resolución de conflictos existentes en nuestro ordenamiento, su tipología, ya sean conflictos de jurisdicción positivos o negativos, procedimiento y órgano competente para su resolución. Finaliza con varios ejemplos de cuestiones prácticas que hacen surgir a día de hoy este tipo de conflictos en los que veremos como en algunos supuestos la normativa administrativa tiene que ceder a los principios rectores del procedimiento concursal, lo que ha supuesto que se haya producido una disminución de ciertos privilegios tradicionales que ostentaba la Administración Pública.

Le contrat de prestations logistiques - Albiol, Morgane (Aix-Marseille Université, 2014)

Le contrôle du respect de la convention du travail maritime en France - Alonso, Loana (Aix-Marseille Université, 2014)

La place du courtage et son incidence sur le marché gabonais de l'assurance - Andeme Owono, Michelle Julie (Institut International des Assurances (IIA), 2014)

Analyse de l'audit interne dans une compagnies d'assurance : Cas du GTAC2A-IARDT - Ayitey, Amah Mokpokpo (Institut International des Assurances (IIA), 2014)

Le statut d'opérateur économique agréé - Balladur, Clarisse (Aix-Marseille Université, 2014)

La gestion des sinistrés en assurance dommages : Quels leviers d'amélioration de la performance opérationnelle pour une gestion efficiente? - Bassan, Bagnon (Institut International des Assurances (IIA), 2014)

La coopération interportuaire sur l'Axe Seine : l'action d'HAROPA - Bessiere, Arnaud (Aix-Marseille Université, 2014)

L’évolution de la responsabilité et de la coresponsabilité du donneur d’ordres : la nécessité du contrôle de la sous-traitance - Boulgarian, Mathilde (Aix-Marseille Université, 2014)

Le développement et les enjeux du transport fluvio-maritime français et européen - Bouvattier, Margaux (Aix-Marseille Université, 2014)

La responsabilité des gestionnaires de ports maritimes à l'égard des propriétaires et exploitants de navires - Boyer, Gabrielle (Aix-Marseille Université, 2014)

Incidences de l'augmentation du SMIG en Côte D'Ivoire et des modifications du code CIMA relatives à l'indemnisation des victimes des accidents de la circulation sur une compagnies d'assurances : Cas de SAHAM assurance - Chigata, Abdoul Karim Coulibaly (Institut International des Assurances (IIA), 2014)

La contribution de la vente de proximité au développement de l'assurance vie : Cas de la SONAR-vie - Dahani, Zéid (Institut International des Assurances (IIA), 2014)

Les leviers fiscaux à la disposition des transporteurs maritimes français de marchandises - Dauphin, Ogier (Aix-Marseille Université, 2014)

Les normes prudentielles d'une compagnie d'assurances : Cas du marché malien - Denon, Modibo (Institut International des Assurances (IIA), 2014)

La bancassurance, un relais de croissance dans la zone CIMA : Cas de Saham assurance Togo - Djigbodi, Akata Koffi (Institut International des Assurances (IIA), 2014)

La nécessité du contrôle de gestion dans une société d'assurance : Cas de la générale des assurances assurances du Bénin-GAB-SA. - Djivo, Seddo Jean Daniel (Institut International des Assurances (IIA), 2014)

L'importance des Etats statistique dans la gestion rationnelle d'une compagnie d'assurance non vie en zone CIMA - Ehoussou, Narcisse (Institut International des Assurances (IIA), 2014)

L'article 13 et la branche transport maritime de marchandises dans l'espace CIMA : Cas du Sénégal - Gueye, Mor (Institut International des Assurances (IIA), 2014)

Les enjeux d'une couverture universelle santé pour l'assurance maladie : cas du Niger - Idrissa Amadou, Hama (Institut International des Assurances (IIA), 2014)

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

Stratégie pour l'amélioration de la souscription des contrats multirisque habitation dans une compagnie d'assurance : Le cas SAHAM assurance Côte d'Ivoire - Kakou Kamenan, Antoine (Institut International des Assurances (IIA), 2014)

L'arbitrage maritime : une étude comparative entre Londres et Paris - Khaldi, Jihane (Aix-Marseille Université, 2014)
Keywords: Arbitrage; Arbitration

L'affrètement coque nue du navire et la location d'aéronef - Leroux, Matthieu (Aix-Marseille Université, 2014)

La responsabilité du transporteur maritime international de marchandise en droit chinois - Liu, Chang (Aix-Marseille Université, 2014)

Les Energies Marines Renouvelables - Louis Torres, Florian (Aix-Marseille Université, 2014)

Amélioration d'un programme de réassurance des compagnies d'assurances de la CIMA : Cas de NSIA Congo - M' Banga, Pierre Jean Blarde (Institut International des Assurances (IIA), 2014)

Les navires abandonnés dans les ports et les voies de recours de l'autorité portuaire - Martin, Camille (Aix-Marseille Université, 2014)

L'obligation d'assurances construction en république du Congo : Bilan et perspectives - Mayina Nkuikidi, Simon (Institut International des Assurances (IIA), 2014)

Le Registre International Français - Meffre, Paul (Aix-Marseille Université, 2014)

La garde privée sur les navires de commerce - Meggiolaro, Léa (Aix-Marseille Université, 2014)

A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa

Développement stratégique et opérationnel de la bancassurance en zone CIMA : Cas d'atlantique assurance IARD et d'atlantique assurance vie - N'golo, Sanogo (Institut International des Assurances (IIA), 2014)

La nécessité du contrôle du fond de roulement au sein d'une société d'assurance : Le cas de NSIA Gabon - Ndong Bekale Ella, Paul Wilfried (Institut International des Assurances (IIA), 2014)

La problématique des appels d'offres d'assurance au Cameroun - Nguemdjop Tchienang, Casimir Raul (Institut International des Assurances (IIA), 2014)

A critical discussion on foreign direct investment in the multilateral trade system and development in SADC - Nhlakanipho, Macmillan Zikalala (University of KwaZulu-Natal, 2014)
Development is understood to be an economic process that aims at a constant improvement of the well-being of all individuals who have the right to participate and benefits from the fruits of development. Development is also a right that requires a progressive realisation by governments, international communities and private sectors to the satisfaction of all individuals. A progressive realisation of this right requires a vibrant economy, which can be acquired through International trade and Foreign Direct Investment (FDI). It is in this context that this thesis has attempted to discuss the influence of FDI and International trade on development. The discussion was initiated by focusing on the history of the multilateral trade system (MTS) by looking at various Ministerial rounds of both the General Agreement on Tariffs and Trade (GATT) and the World Trade Organisation (WTO). In this discussion the thesis found that, whilst there are various multilateral political frameworks regulating trade, FDI is subject to regional and domestic political frameworks. The thesis also discussed development in relation to the millennium development goals (MGDs). It was established the goal eight of the MDGs requires the integration of poor countries into the MTS so that they can be able to exploit their comparative advantage. This goal influenced the launching of the Doha Development Agenda (DDA) at the Doha round in 2001. However, the thesis also established that conclusion of the DDA has been progressing at a slow pace. Therefore it has not yielded substantial results for poor countries. The failure to conclude the DDA has led to an increase of Regional Trade Agreements (RTAs), which some scholars view as a supplement of multilateral trade integration. However, the SADC region has not been able to conclude their integration objectives due to the fact that many member states belong to other RTAs. In the case of FDI the thesis established that FDI is accompanied by a wide range of resources for host countries, which can be utilised for enhancing development. However, it was also established that the SADC has not been able to attract lucrative FDI due to a wide range of factors that impede FDI. On this finding, a case study was employed on four countries in the region, namely Angola, Botswana, South Africa and Zimbabwe.
Keywords: Economic Policy; FDI; Foreign direct investment; International Trade; International economic relations; Investments

L'impact de la qualité de gestion des sinitrés sur la performance d'une compagnie d'assurance : Le cas du dossier transport - Niane, Mamadou (Institut International des Assurances (IIA), 2014)

La gestion des risques climatiques : Un marché pour l'assurance? - Nonfodji, Evariste Mamert B. (Institut International des Assurances (IIA), 2014)

Nécessite et mise en place d'un système de contrôle de gestion dans une compagnie d'assurance : cas d' UA-Vie Cote d'ivoire - Odje, Koffi martial (Institut International des Assurances (IIA), 2014)

L'Assurance de responsabilité civile du transporteur de marchandises - Ombolo Menoga (Ombolo Menoga, 2014)

Les obligations des transporteurs ferroviaire et routier à l'épreuve des reglements passagers - Paresys-Barbier, Mathilde (Aix-Marseille Université, 2014)

Mediación mercantil. Mediación mercantil empresarial - Rojas Roldán, María de la Encarnación (Universidad Internacional de Andalucía, 2014)
Trabajo de Curso de Experto Universitario en Mediación Civil, Familiar, Mercantil y Organizaciones Complejas (2013). Tutora: María Sonia González Ortega. El objetivo del presente trabajo es abordar la Mediación en el seno de las organizaciones, teniendo en cuenta que estas constituyen sistemas de interrelación entre personas, donde confluyen numerosos intereses. Se trata por tanto, de abordar la resolución de los problemas no solo existentes sino de los emergentes, aportando herramientas eficaces en el desarrollo de la actividad empresarial, que permitan gestionar y modular los conflictos, de forma que los mismos, se transformen en oportunidades de mejora y de crecimiento empresarial.
Keywords: Mediación; Mediation; Médiation

Les innovations en assurance vie : Une nécessité au regard des contraintes techniques et commerciales du marché burkinabe - Saba, Amadou (Institut International des Assurances (IIA), 2014)

Le règlement Bruxelles I et le problème de la compétence juridictionnelle en droit du transport maritime - Shirvanzada, Lamiya (Université Paul Cézanne Aix-Marseille 3, 2014)
Le droit communautaire est un droit en évolution intensive. Les règles de compétence, d’exécution et de reconnaissance en sont une parfaite illustration dans le cadre du Règlement Bruxelles I qui est refondu dans un nouveau Règlement. Cette recherche dispose d’une importance quant à l’analyse des questions procédurales soulevées dans le domaine du transport maritime. En effet, les règles de compétence énoncées par lesdits textes, au cas où ils sont applicables, touchent des spécificités propres au transport maritime à savoir la fréquence des clauses attributives figurant dans les connaissements et le caractère tripartite du contrat de transport maritime. De plus, les règles au service de la coopération judiciaire, telles que la litispendance et la connexité, sont utiles pour pallier, dans une certaine mesure, des controverses pouvant découler de ces mêmes règles communautaires. En tout état de cause, le transport maritime marque sa spécificité quant à l’opposabilité de ces clauses envers les différents acteurs de l’opération de transport.
Keywords: Anti-suit injunction; Clauses attributives de juridiction et validité; Connexité; Litispendance; Opposabilité des clauses attributives de juridiction; Règlement Bruxelles I (refondu); Règles de compétence

Le développement et la gestion de l'assurance transports/ facultés au Cameroun - Sibe Bessong, Jérôme Daniel (Institut International des Assurances (IIA), 2014)

Copyright and developing countries a critical examination of recent developments in copyright law with particular reference to the impact on developing countries and access to educational materials - Siphepho, Nomvuyo Nicole (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Copying processes; Copyright; Developing countries; Instructional materials industry

La nécessité de contrôle de gestion dans une société d'assurance non vie : : cas de la société nigérienne d'assurances et de réassurances (SNAR LEYMA) - Souley, Soumeye abdourahame (Institut International des Assurances (IIA), 2014)

L'expert en marchandise transportée par voies terrestres - Taffe, Marie (Aix-Marseille Université, 2014)

Les appels d'offres d'assurance au Cameroun - Tchienang, Casimir Raul Nguemdjop (Institut International des Assurances (IIA), 2014)

La gestion des sinistrés; outil de performance et de rentabilité d'une compagnie d'assurance IARDT : Cas de AMSA assurances Sénégal - Thiam, Alia (Institut International des Assurances (IIA), 2014)

L'organisation internationale du transport maritime de lignes régulières - Tourneur, Margaux (Université Paul Cézanne Aix-Marseille 3, 2014)

Les dommages causés par les coI - Veidig Favarel, Marie (Université Paul Cézanne Aix-Marseille 3, 2014)

La présomption de responsabilité du titulaire du certificat d'immatriculation - Viaux, Poehere (Aix-Marseille Université, 2014)

Le rating des sociétés d'assurance - Wabo Kamgaing, Pascal (Institut International des Assurances (IIA), 2014)

La loi applicable à l'action des tiers au contrat de transport et autres intervenants de l'expédition maritime - Zerrouki, Michael (Aix-Marseille Université, 2014)
Keywords: Abordage; Action directe (délit); Conflict of laws; Conflit de lois; Contrat d'assurance; Contrat de commission de transport; Contrat de manutention; Contrat d’affrètement; Contrat d’engagement maritime; Tiers au contrat de transport